2011
DOI: 10.1097/brs.0b013e3181fea1ed
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Cardiac and Pulmonary Function Decline in Patients With Duchenne Muscular Dystrophy

Abstract: Study Design Retrospective review of scoliosis progression, pulmonary and cardiac function in a series of patients with Duchenne Muscular Dystrophy (DMD). Objective To determine whether operative treatment of scoliosis decreases the rate of pulmonary function loss in patients with DMD. Summary of Background Data It is generally accepted that surgical intervention should be undertaken in DMD scoliosis once curve sizes reach 35 degrees to allow intervention before critical respiratory decline has occurred. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 29 publications
6
38
0
Order By: Relevance
“…However, there is relatively little data on predictors of lung function. Scoliosis represents a risk factor for worsening restriction, but it is not clear if surgery to correct it slows the rate of lung function decline . Previous research has suggested that oral corticosteroid treatment may slow the rate of lung function decline without an observed increase in BMI.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is relatively little data on predictors of lung function. Scoliosis represents a risk factor for worsening restriction, but it is not clear if surgery to correct it slows the rate of lung function decline . Previous research has suggested that oral corticosteroid treatment may slow the rate of lung function decline without an observed increase in BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In our experience the most severe patients with NMS are not able to perform reliable tests with a spirometer because of poor cooperation. Furthermore, most of the lung function studies have been performed among Duchenne muscular dystrophy patients and these results should therefore not be generalized to all neuromuscular patients [7, 9–11, 13, 14]. …”
Section: Discussionmentioning
confidence: 99%
“…By age 10–12, more than 70% of boys lose ambulation. Many patients require noninvasive ventilator support at night by age 15, with death any time after age 20 related to pneumonia or cardiomyopathy . The natural history of the disease is significantly changed with the use of glucocorticoids.…”
Section: Defining the Natural History Of Dmdmentioning
confidence: 99%